Effect of Surface Nanostructuring on Gene Expression for Protein Synthesis, Osteoblast Cells Recruitment and Size of Focal Adhesion: A Review - Raj N.; Agrawal R.; Chattopadhyay K.; Bansal R.; Singh V. (My University, 2025)
Dental implants provide oral rehabilitation by mimicking bone topography, faster bone formation, and rapid bone healing to enable early loading protocol with better stability. The dental implant surface affects the mechanical stability of the implant affecting cell adhesion and osteogenic cell response. Different techniques have shown biological advantages through increase in surface wettability, surface roughness, and altered surface topography. These have benefitted osseointegration in both healthy as well as a compromised bone through its underlying cellular mechanisms. The effects of nanostructuring are discussed in this chapter in terms of gene expression, biochemical stimuli, biocompatibility, corrosion resistance, cell metabolism, and its differentiation. © 2022 Apple Academic Press, Inc.